TRADITIONAL SURGICAL INTERVENTIONS FOR LIVER ECHINOCOCCOSIS AND RISK FACTORS FOR DISEASE RECURRENCE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Recurrence of liver echinococcosis is due to the influence of many factors, the degree of influence of some of which may be offset by the influence of other factors. An effective measure to prevent relapse of liver echinococcosis after surgical treatment, subject to the principles of aparasitic and antiparasitic, is anti-relapse therapy with Albendazole.